First record of petrified Permian pecopterids from the Parana Basin, Brazil (Corumbatai Formation, Passa Dois Group, northeastern State of São Paulo): Morphology, anatomy and paleoecological implications - Tavares, Tatiane M. V. [UNESP]; Rohn, Rosemarie [UNESP] (Pergamon-Elsevier B.V. Ltd, 2009)
Petrified pecopterids are described for the first time in the Parana Basin. They were collected at an outcrop of the Corumbatai Formation (Passa Dois Group, Middle Permian) in the Municipality of Piracicaba (State of São Paulo, Brazil). The assemblage is composed of Pecopteris taguaiensis Rohn and Rosler, 1986, Pecopteris sp. 1, Pecopteris sp. 2 and Pecopteris sp. 3. An emendation to the diagnosis of P. taguaiensis is proposed on the basis of the characteristics shown by the preserved three-dimensional external leaf morphology and partially by the epidermis (not available in the previously described impressions). The small size of the pinnules, the thick, downward-rolled leaf lamina, the thick veins, the straight walls of the epidermal cells, and the trichomes of the four pecopterid taxa may be interpreted as xeromorphic features developed in response to relatively dry climatic conditions and/or direct incidence of the sunlight. The leaves were impregnated with silica before the final burial, considering that they are fragmented, not deformed and associated with angular breccia clasts. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Pecopteris; Pteridophylla; Ferns; Palaeobotany; Corumbatai Formation; Parana Basin; Permian; Xeromorphism